Violence against Journalists and Impunity - Ugaz Sánchez-Moreno, José (2008)
This paper is about the journalists’ situation, especially of the investigation, who are likely to suffer violence acts because of their free exercise of their profession. It been said that this situation is present in the majority of the Latin American countries, it is important to note that it is not present in the authoritarian regimes only, but in the democratic regimes too. In addition, something that is pointed is the impunity that follows this violence due to the deficient criminal system performance in the investigation and sanction of those acts. This paper focuses in countries such as Mexico and Colombia, who are the most characteristic in the region. From a regulation point of view, both countries enshrined the guarantee and protection of the free exercise of journalism and investigation, as well as the repression of whom attack the journalists. In turn, from an institutional point of view that ensure the law enforcement we can say that both countries have the basic organisms to achieve that purpose. However, there is not a properly response of the criminal system to the violence acts against the journalists. In Mexico it been identified that the aggressors came from the organized crime or the drug trafficking and the reasons of the attacks would be to silence the ongoing investigations. The impunity in the Mexican system does not seems over this acts only, but constitutes an expression of an institutional weaknesses. In Colombia there is a low tendency of murders, but a raising of the threats in order to undermine the free exercise of the profession. The aggressions, generally, came from the paramilitary groups whom wants to avoid that the political links will disclosed.  As with the Mexican system, an institutional weakness avoid a full investigation of those cases.  Because of this situation of aggression and impunity, there is a self-censorship scenario. In this way, it been said that is not the lack of regulation or institutions what causes the impunity situation, but the lack of political will to create the conditions that allow the investigations. Finally, the author recommend implementing a specialized subsystem in the prosecution and judicial areas that knows exclusively the crime against journalists.  In addition to these, he elaborates a couple of recommendations for the system to function properly.